Mujeres, derechos y política: el Partido Peronista Femenino en el mundo rural de Misiones: Women, rights and politics: the Peronist Women's Party in rural Misiones (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
This study examines the formation and actions of the Peronist Women’s Party (PPF) in promoting labor rights for yerba mate workers in Misiones during early Peronism. The temporal scope focuses on the mid-20th century, highlighting key legal milestones: the Rural Workers’ Statute (1944), Law 13.020 for temporary rural workers (1947), and the women’s suffrage law, 13.010 (1947). Based on these legal frameworks, the study analyzes the interplay between labor policies, the institutionalization of the Secretariat of Labor and Social Welfare (STP), and the establishment of the PPF in Misiones. The research draws on national and regional historiography and develops two case studies: Cerro Corá and Montecarlo. The analysis sheds light on the relations among Peronism, women, rurality, and labor rights, offering a critical perspective on the implementation of labor policies and women’s organizational structures in rural spaces.